2018
DOI: 10.5194/tc-2018-221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the snowmelt-albedo feedback at Neumayer Station, East Antarctica

Abstract: Abstract. We quantify the snowmelt-albedo feedback at Neumayer Station, East Antarctica, using 24 years (1992–2016) of high-quality meteorological observations to force a surface energy balance model. The modelled 24-year cumulative surface melt at Neumayer amounts to 1060 mm water equivalent (w.e.), with only a small uncertainty (± 3 mm w.e.) from random measurement errors. Results are more sensitive to the chosen value for the surface momentum roughness length and fresh snow density, yielding a range of 800–… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 46 publications
(52 reference statements)
2
20
0
Order By: Relevance
“…The choice of fresh snow grain size is limited by the availability of look‐up tables for the dry snow metamorphism d r e,dry (see also Jakobs et al. (2019)); the refrozen snow grain size provided the best comparison with observations (Van Wessem et al., 2018). Furthermore, f o , f n , and f r are the fractions of old, fresh and refrozen snow.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The choice of fresh snow grain size is limited by the availability of look‐up tables for the dry snow metamorphism d r e,dry (see also Jakobs et al. (2019)); the refrozen snow grain size provided the best comparison with observations (Van Wessem et al., 2018). Furthermore, f o , f n , and f r are the fractions of old, fresh and refrozen snow.…”
Section: Methodsmentioning
confidence: 99%
“…(2011) and Jakobs et al. (2019), who used more than two layers to calculate the surface albedo. Equations for d α u , d α τ , d r e,dry , d r e,wet and A can be found in Gardner and Sharp (2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Holland et al (2011) and Kuipers Munneke et al (2014b) suggested that modelled firn air content on large parts of Larsen C ice shelf is too low, caused by either meltrates that are overestimated, or accumulation rates that are too low, or both. This can also be related to how deep the meltwater penetrates into the firn and how important the sensitive melt-albedo feedbacks (Jakobs et al, 2018) is. Obviously, to tackle these problems, more observational constraints are needed.…”
Section: Firn Air Content Lateral Meltwater and Superimposed Icementioning
confidence: 99%